2011
DOI: 10.1177/1744259111411652
|View full text |Cite
|
Sign up to set email alerts
|

Thermal response of basement wall systems with low-emissivity material and furred airspace

Abstract: http://www.nrc-cnrc.gc.ca/ircThe material in this document is covered by the provisions of the Copyright Act, by Canadian laws, policies, regulations and international agreements. Such provisions serve to identify the information source and, in specific instances, to prohibit reproduction of materials without written permission. For more information visit http://laws.justice.gc.ca/en/showtdm/cs/C-42Les renseignements dans ce document sont protégés par la Loi sur le droit d'auteur, par les lois, les politiques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 7 publications
3
43
0
Order By: Relevance
“…For example, in Figure 10b for an enclosed airspace having a thickness of 13 mm (T avg = 10.0 o C, T = 16.7 o C), it is shown that increasing H from 8 in (203.2 mm) (A R = 16) to 88 in (2,235.2 mm) (A R = 172) resulted in an increase in the R-value by 20.3% at  eff = 0.03. This observation is in agreement with results from previous studies [7,9].…”
Section: Comparison Between R-values Predicted By Model and Listed Insupporting
confidence: 83%
See 2 more Smart Citations
“…For example, in Figure 10b for an enclosed airspace having a thickness of 13 mm (T avg = 10.0 o C, T = 16.7 o C), it is shown that increasing H from 8 in (203.2 mm) (A R = 16) to 88 in (2,235.2 mm) (A R = 172) resulted in an increase in the R-value by 20.3% at  eff = 0.03. This observation is in agreement with results from previous studies [7,9].…”
Section: Comparison Between R-values Predicted By Model and Listed Insupporting
confidence: 83%
“…For an enclosed airspace of  = 13 mm (H = 12 in (304.8 mm)) and for the "1-Cavity" case, Figure 6 shows that the predicted R-values are in good agreement with R-values of the ASHRAE table for In recent studies [7,9], the contribution of Furred-Airspace Assembly (FAA) to the R-values of wall systems with horizontal furring and vertical furring of the same center-to-center spacing were investigated. The FAA was attached to EPS layer (1 in (25.4 mm) thick), which was bonded by Low Emissivity Material (LEM) facing the airspace (1 in (25.4 mm) thick).…”
Section: Comparison Between R-values Predicted By Model and Listed Insupporting
confidence: 65%
See 1 more Smart Citation
“…Many studies were conducted to determine the R-values of RI products, and wall and roofing systems incorporating RI products (Yarbrough 1983, Fairey 1985, Han et al 1986, Desjarlais and Tye 1990, Desjarlais and Yarbrough 1991, Medina 2000, Al-Homoud 2005, European Commission 2010, Saber and Swinton 2010, Craven and Garber-Slaght 2011, Saber et al 2011b,c, Vrachopoulos et al 2012, D'Orazio et al 2012, Saber and Maref 2012,b,c, Escudero et al 2013, Tenpierik and Hasselaar 2013, Saber 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…The present model was also benchmarked against GHB test results [24] and then used to conduct numerical simulations to investigate the effect of foil emissivity on the effective thermal resistance of different wall systems with foil bonded to different types of thermal insulations placed in furred-airspace assemblies, in which the foil was adjacent to the airspace [20,23,26]. Recently, this model was benchmarked against the test data of different types of reflective insulations [28][29] that were obtained using the ASTM C-518 test method, and then used to examine the thermal performance of different types of reflective insulation assemblies.…”
Section: Model Description and Previous Compariason With The Measuredmentioning
confidence: 99%